1993
DOI: 10.1161/01.cir.88.3.961
|View full text |Cite
|
Sign up to set email alerts
|

Detailed angiographic analysis of high-speed mechanical rotational atherectomy in human coronary arteries.

Abstract: BACKGROUND Several types of atherectomy devices have been developed recently for treatment of patients with ischemic heart disease. METHODS AND RESULTS Mechanical rotational atherectomy (MRA) using a high-speed rotational burr (Rotablator) was performed on 116 lesions in 104 patients. MRA alone was performed in 27 lesions (23%), and conventional balloon angioplasty (PTCA) was performed after MRA in 89 lesions (77%). Diameter stenosis decreased from 70 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(33 citation statements)
references
References 24 publications
5
28
0
Order By: Relevance
“…Safian et al [7] reported Q-wave myocardial infarction following rotational atherectomy to be 4.8% and side branch occlusion to be 2.7% in a series of 116 lesions when both rotational atherectomy and balloon angioplasty were used together, as was done in our patient. Although most would agree that adjunctive balloon angioplasty should be performed following rotational atherectomy to increase immediate patency and treat complications such as dissection [7,8], Safian et al 171 noted that restenosis, which in their study was 51% at 3-6 mo, was not prevented.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Safian et al [7] reported Q-wave myocardial infarction following rotational atherectomy to be 4.8% and side branch occlusion to be 2.7% in a series of 116 lesions when both rotational atherectomy and balloon angioplasty were used together, as was done in our patient. Although most would agree that adjunctive balloon angioplasty should be performed following rotational atherectomy to increase immediate patency and treat complications such as dissection [7,8], Safian et al 171 noted that restenosis, which in their study was 51% at 3-6 mo, was not prevented.…”
Section: Discussionsupporting
confidence: 57%
“…Although most would agree that adjunctive balloon angioplasty should be performed following rotational atherectomy to increase immediate patency and treat complications such as dissection [7,8], Safian et al 171 noted that restenosis, which in their study was 51% at 3-6 mo, was not prevented.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs frequently following thrombolytic or mechanical reperfusion for acute myocardial infarction and in the setting of unstable angina [3,7,8]. It is most common during use of rotational atherectomy [9,10] and during PCI in saphenous vein grafts [2]. The purpose of this review is to define the angiographic appearance and clinical outcomes of no-reflow and to summarize the various treatment and prevention options currently available to the interventional cardiologist.…”
Section: Introductionmentioning
confidence: 99%
“…flap, or emboli in affected arteries [5,7,11,13,161. Despite the 5 years of widespread application of this treatment mode, the technique of HSRA is still subject to individual operator variation, both in stand alone and in adjunctive balloon angioplasty procedures.…”
Section: Introductionmentioning
confidence: 99%